IMPLEMENTATION OF STORYTELLING METHOD IN LEARNING TO READ AND WRITE THE QUR'AN FOR THE FORMATION OF STUDENTS' CHARACTER AT TPQ AISYIYAH KEPATIHAN - Haris, Achmad; Amirudin, Noor (LP2M IAI Al-Khairat Pamekasan, 2024)
The aim of this research is to obtain an overview of the implementation of the storytelling method in learning to read and write the Qur'an for the character formation of students at TPQ Aisyiyah Kepatihan. This is qualitative research that focuses on a phenomenological approach. This research was carried out carefully, in a structured manner, and continuously. The data obtained in this research is descriptive, consisting of words and observable behavior. The aim of this research is to explain various subjects or subject situations clearly and concisely. To obtain accurate data for this research, researchers came to TPQ Aisyiyah Kepatihan, Menganti-Gresik, to obtain the data. Researchers use the following data sources: 1) Data sources are primary data, data directly from the research location, or the first source of research subjects. Like a TPQ ustadzah 2) Secondary data sources are data that researchers have personally collected to support primary sources. It can be said that the data is organized in the form of documents. The research results show that there are three stages: planning, implementation, and evaluation. The ustadzah or teacher must prepare the following steps in the planning process: choosing the material to present, comprehending the material's main points, selecting material that meets the needs of the students, choosing props, and determining seating arrangements. Second, in its implementation, there are several stages: Opening for 5 minutes, reading Iqro' for 25 minutes, listening to the story for 45 minutes, reflection for 10 minutes, closing for 5 minutes. The last one is evaluation. There are two stages of reflection and observation. For reflection, it is carried out directly after the ustadzah has finished telling the story, and for observation of the results of the learning process, it is notified to the student's guardian once a month. The students are very enthusiastic to hear the story from the ustadzah.